Characterization of adenine nucleotide metabolism in the cellular model of Huntington's disease. (2nd November 2018) - Toczek, Marta; Pierzynowska, Karolina; Kutryb-Zajac, Barbara-; Gaffke, Lidia; Slominska, Ewa M.; Wegrzyn, Grzegorz; Smolenski, Ryszard T.
Abstract: Huntington's disease (HD) is a neurodegenerative disorder that is caused by expanded CAG repeats within the exon-1 of the huntingtin (HTT) gene. It has been shown that HTT interacts with the proteins involved in the gene transcription, endocytosis and metabolism, nevertheless the biochemical pathways by which mutant HTT causes a cellular dysfunction remain unclear. Thus, this study aimed to establish the role of mutant HTT expansion in energy and nucleotide metabolism deteriorations. We examined HEK 293 T cell line transfected with plasmids expressing wild-type (control) or mutant exon 1 of the HTT gene (HD). Analysis of intracellular concentration of adenosine triphosphate (ATP) and nicotinamide adenine dinucleotide (NAD + ), as well as activities of intra- and extracellular enzymes of nucleotide catabolism (such as adenine monophosphate deaminase (AMPD), adenosine deaminase (ADA), purine nucleoside phosphorylase (PNP) and ectonucleoside triphosphate diphosphohydrolase (eNTPD), ecto-5′-nucleotidase (e5NT), ecto-adenosine deaminase (eADA) were performed with high pressure liquid chromatography. Protein concentration was measured with Bradford method. We found diminished intracellular ATP concentration (22.5 ± 1.7 in HD; 29.3 ± 1.4 nmol/mg protein in control), increased ADA activity (27.9 ± 1.0 in HD; 21.1 ± 1.6 nmol/min/mg protein in control) and reduced activities of eNTPD (2.4 ± 0.5 in HD; 5.8 ± 0.7 nmol/min/mg protein in control), e5NT (0.1 ± 0.01 in HD; 0.2 ± 0.01 nmol/min/mg protein in control) and eADA (0.3 ± 0.03 in HD; 0.4 ± 0.04 nmol/min/mg protein in control) while NAD + concentration, AMPD and PNP activities remained unchanged. This study highlights that the mutant HTT expansion resulted in depletion of cellular ATP concentration and reduced rates of extracellular nucleotide breakdown. In conclusion, such changes may contribute to the pathology of HD.